Current Advances in the Development of Decellularized Plant Extracellular Matrix - Zhu, Yiwei; Zhang, Qi; Wang, Shengyu; Zhang, Jianfeng; Fan, Shunwu; Lin, Xianfeng (Frontiers in Bioengineering and Biotechnology, 2021)
An imbalance exists between the supply of organs for transplantation and the number of patients in the donor transplant waiting lists. Current use of autologous, synthetic, and animal-derived grafts for tissue replacement is limited by the low availability, poor biocompatibility, and high cost. Decellularised plant scaffolds with remarkable physical similarities to human organs have recently emerged and have been found to present favourable characteristics that make them suitable as an alternative biomaterial, such as a superficial areasurface, excellent water transport and retention, pre-existing vascular networks, interconnected porosity, and a wide range of mechanical properties. In addition to their unique and superior biocompatibility, plant-derived scaffolds present the advantages of low production cost, no ethical or supply constraints, simple operation and suitability for large-scale production and research. However, there are still some problems and deficiencies in this field, such as immature decellularization standards and methods and insufficient research on the biocompatibility of plant extracellular matrix. At present, research on decellularised plant extracellular matrix is still in its infancy, and its applicability to tissue engineering needs to be further improved. In this review, the current research progress on decellularised plant scaffolds is reviewed, and the problems to be solved and future research directions are discussed.